2004
DOI: 10.1111/j.1471-5740.2004.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of food worker transmission of foodborne pathogens: risk assessment and evaluation of effective hygiene intervention strategies

Abstract: The infected food handler can be responsible for the transmission of infectious intestinal diseases (IID) caused by foodborne pathogens. It is believed that personal hygiene practices with varying levels of complexity can help prevent foodborne pathogens from entering the food chain. Overall, it has been difficult to reach a consensus among stakeholders on precisely which intervention measures should be employed in food handling environments to effectively reduce IID rates. Through a study of over 300 reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 106 publications
(105 reference statements)
6
55
0
Order By: Relevance
“…Though no other studies to date that we know of have quantified the relationships of microbes between hands and produce in the agricultural environment, this implication is consistent with those of other studies suggesting that hands are an important vehicle of contamination of produce (13,(33)(34)(35)(36). We hypothesize that microorganisms measured in our study could have been transferred either from hands to produce or produce to hands, as has been demonstrated to occur (33,(37)(38)(39). These findings and our hypothesis led to testing the effectiveness of hand hygiene interventions (soap, hand sanitizer) to improve the microbial quality of hands and produce (33,34).…”
Section: Discussionsupporting
confidence: 80%
“…Though no other studies to date that we know of have quantified the relationships of microbes between hands and produce in the agricultural environment, this implication is consistent with those of other studies suggesting that hands are an important vehicle of contamination of produce (13,(33)(34)(35)(36). We hypothesize that microorganisms measured in our study could have been transferred either from hands to produce or produce to hands, as has been demonstrated to occur (33,(37)(38)(39). These findings and our hypothesis led to testing the effectiveness of hand hygiene interventions (soap, hand sanitizer) to improve the microbial quality of hands and produce (33,34).…”
Section: Discussionsupporting
confidence: 80%
“…Food workers may transmit pathogens to food coming from a contaminated surface of another food, or from hands contaminated with organisms from their gastrointestinal tract. This is also supported by report in which about 89% of outbreaks caused by food contamination by food workers, pathogens were transferred to food by workers' hands (Michaels et al, 2004).…”
Section: Personal Hygiene Practicessupporting
confidence: 68%
“…In terms of message development, the findings of this study suggest that interventions might focus on developing messages to strengthen injunctive norms at a given center. Similar to the situation in hospitals and food preparation contexts (Creedon, 2005;Michaels et al, 2004;Pittet, 2001), hand hygiene policies and enforcement in child care centers did not explain significant variance in reported handwashing. Thus, this study focused on the influence of social norms on reported handwashing, and found significant effects.…”
Section: Applications For Health Communication Interventionsmentioning
confidence: 64%